Influence of demographics on saving behavior: a case in jaffna district - Karunaanithy, K.; Santhirasekaram, S. (University of Jaffna, 2018)
Household saving is a crucial determinant of welfare as it has a smoothening effect on unforeseen fluctuations in income. Though, many factors can shape up the saving behavior, this study mainly focuses on demographic factors, with the aim to delineate their effect on household savings. A questionnaire method was used to collect data from 500 households under a survey method. With the objective of finding out the association of Age, Sex, Region, Education, Family Size, Marital Status, Family Type, Job Categories, Type of Village, Religion, Age At Marriage, House owner ship, Number of Earners, Number of Non-Earners on savings, this study applied One way ANOVA (F test) for Earner and Non- Earner variables and non - parametric tests such as Kruskal-Wallis Test and Jonkheere- Terpstra Test for the others as they showed non-linearity which calls for non- parametric tests. The test results revealed that the mean household Savings does significantly differ across different Regions of the Jaffna District, Level of Education of the Head, Job categories of the Head, Type of Village, Religion, Age at Marriage, Number of Earners, and Number of Non-Earners. Meanwhile, savings does not differ significantly across Age, Sex, Family size, marital status, and Family type. Hence null hypotheses were accepted for these variables that there were no apparent differences in saving across these five variables. Since saving is a tool for development Initiatives, these findings would be of policy significance to Jaffna District while formulating policies to improve personal saving behavior or to develop product and policies to promote regular savings.
Keywords: Demographic variables; Household savings; Mean difference